Estetik dalam buku cerita bergambar kanak-kanak di Malaysia - Kaithiri, Arumugam (2021)
Children’s picture storybooks are a special form of literary work as the meaning of the story is created through the relationship between text and pictures. This speciality enables children's picture storybooks to be considered as literary works of high aesthetic value. However, children's picture storybooks in Malay has received less attention among the Malaysian community. There are parents who are willing to buy children's picture storybooks from abroad as reading material for children. This phenomenon shows the level of awareness among the Malaysian community regarding the uniqueness of children's picture storybooks in Malay which remains at a discouraging level. In this regard, this study aims to identify the genres and children’s picture storybooks in the Malay-language published in Malaysia between 2010 and 2020, and subsequently discuss the aesthetic elements found in the book. This study has analysed a total of 83 children's picture storybooks covering five genres, namely the animal stories, folklore, fantasy, adventure and realistic genres. Nikolajeva’s (2006) aesthetic approach and A. Aziz Deraman’s (2001) cultural approach were used to discuss the aesthetic elements in children’s picture storybooks by using text and picture content analysis methods. Findings of the study show that children's picture storybooks in Malay published in Malaysia do have aesthetic elements as presented by Nikolajeva (2006) which includes background aesthetics, character aesthetics, narrative perspective aesthetics, time and movement aesthetics, figurative language aesthetics, metaphysics and intertext, as well as the aesthetics of paratext in pictorial storybooks. In addition, the findings show that the children's picture storybooks studied also include cultural elements as found in the cultural approach of A. Aziz Deraman (2001) as a new element that highlights the beauty of children's picture storybooks in Malay in Malaysia.